2018
DOI: 10.1017/s0007114518000168
|View full text |Cite
|
Sign up to set email alerts
|

Early effects on the intestinal barrier and pancreatic function after enteral stimulation with protease or kidney bean lectin in neonatal rats

Abstract: Gut maturation naturally accelerates at weaning in altricial mammalian species, such as the rat. Mimicking this, gut development can also be induced precociously, 3-4 d earlier than it would occur naturally, by enteral exposure to phytohaemagglutinin (PHA), or various proteases. We investigated the early effects of gut provocation on intestinal barrier and pancreatic functions, to get a better understanding of the mechanisms that initiate gut maturation. The effects of oral administration of protease (trypsin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Hence, PHA is thought to have blocked epithelial "receptors" needed for endocytosis. In contrast, provocation feeding with a protease caused an instant decrease in receptor-mediated endocytosis, a gradual decrease in the non-specific endocytic pathway and a temporary increase in paracellular leakiness (147).…”
Section: Forms and Routes Of Antigen Transfermentioning
confidence: 82%
See 1 more Smart Citation
“…Hence, PHA is thought to have blocked epithelial "receptors" needed for endocytosis. In contrast, provocation feeding with a protease caused an instant decrease in receptor-mediated endocytosis, a gradual decrease in the non-specific endocytic pathway and a temporary increase in paracellular leakiness (147).…”
Section: Forms and Routes Of Antigen Transfermentioning
confidence: 82%
“…Experiments in neonatal rats have shown that anti-nutritional factors, such as lectins, block intestinal absorption (145), and oral provocation with the lectin PHA severely decreases endocytosis immediately after exposure (146,147), due to the binding to the epithelial surface (146,148,149). Hence, PHA is thought to have blocked epithelial "receptors" needed for endocytosis.…”
Section: Forms and Routes Of Antigen Transfermentioning
confidence: 99%
“…The natural process of gut maturation can be induced precociously by abrupt weaning (Lee and Lebenthal, 1983), corticosteroids (Martín et al, 1993), provocation with pancreatic or pancreatic-like proteases (Prykhodko et al, 2015;Sureda et al, 2018) and polyamines (Dufour et al, 1988;Bekebrede et al, 2020), amongst other factors. Additionally, several studies indicate that a diverse range of medicinal plants and phytochemicals have potential as maturational agents to the developing gut (Supplementary Table 1).…”
Section: Impact Of Medicinal Plants and Phytochemicals On The Development And Maturation Of The Gastrointestinal Tractmentioning
confidence: 99%
“…The intestinal in vivo permeability test in rats was conducted by measuring the absorption of lactulose and mannitol according to Meddings and Gibbons [22,23], as previously described [16]. Concentrations of lactulose and mannitol quantitatively collected in urine were analyzed with the EnzyChromTM Intestinal Permeability Assay Kit (EIPM-100) from BioAssay System (Hayward, CA, USA).…”
Section: Intestinal In Vivo Permeabilitymentioning
confidence: 99%
“…The mucosal thickness was measured in three parts of the small intestine, including the duodenum, middle part of the jejunum and ileum, and in the upper colon of the rats according to previous procedures with some modifications [23,24]. After fixation in 4% paraformaldehyde, all tissue samples were washed with phosphate-buffered saline and cryoprotected with 30% sucrose by incubation for 24 h. All tissues were embedded into cryo-moulds (Sakura, Torrance, CA, USA) using the optimal cutting temperature compound TissueTek®(HistoLab, Gothenburg, Sweden), immediately frozen on dry ice, and stored at −80 • C. The cryosection of animal tissues was performed on a Leica CM1860 Cryostat (Leica Microsystems AB, Germany).…”
Section: Mucosal Thicknessmentioning
confidence: 99%